Cost-effectiveness of a diabetes group education programme delivered by health promoters with a guiding style in underserved communities in Cape Town, South Africa - Kroukamp, Roland (Stellenbosch : University of Stellenbosch, 2016)
Thesis (MMed)--Stellenbosch University, 2014.